1. Simultaneo Ensemble - Bringing Our History Into the Future / A New Pedagogical Approach of Music-Making Developed from "Bottega Dell'arte" - Franchini Cecilia (Sciendo, 2018)
How much can contemporary artists and audiences learn from the past? The mission and activity of Simultaneo Ensemble - SIM - is presented. How SIM laboratory, grouping performers from the seven Music Academies of Veneto, encourages musicians to explore, perform and promote italian music composers and their works. This article will consider the relationship between research into historical concert programs and the creation of adventurous and compelling chamber music concerts for contemporary audiences. Learn how to enhance the position of chamber music activity trough projects that have suceeded in bringing people together toward common goals via the arts.